The Ground Based Geological Assessment of an Active Landslide: A Case Study of Jharlang Landslide in Dhading District, Lesser Himalaya, Central Nepal - K.C., Jharendra; Gautam, Depak; Neupane, Purushottam; Dhakal, Shraddha; Paudyal, Kabi Raj (Journal of Nepal Hydrogeological Association, 2025)
Jharlang Landslide, also known as "Jharlang Pairo," is a large-scale, ongoing landslide that is situated in the northwest of the Dhading District. This article provides a detailed geological assessment and evaluates the causes, consequences and general mitigation plan of the landslide. The overall study of the landslide was carried out by desk study and f ield investigation. Field work was carried out to gather pertinent data and information about slope failures. The primary methods of evaluation are knowledge-driven approaches, kinematic analysis, visual inspection, satellite image interpretation, and topographic maps interpretation. The study facilitates comparative analysis through previous studies, satellite images and field observation. The study area is located in the Lesser Himalayan region in Central Nepal. The dominant lithological units in this area are Meta-sandstone, Ulleri Augen Gneiss and phyllite. The constant risk of the landslide to the local people and damage of farmed land and infrastructures is increasing. The area has been impacted by the "2015 Gorkha Earthquake," which has caused new tension cracks to emerge, slope failures to increase, and landslides to spread toward neighboring settlements. Slope failures in different dimensions are caused by the area's brittle, high density soil masses that lay on top of the weathered Ulleri Augen Gneiss, phyllite, and meta-sandstone.The Jharlang Landslide is a composite of debris flows, debris slides, and rotational slides. The potential and weak section are mostly located in NE and SW direction of the study area. The tension cracks are noticeable that extend towards the villages. The result of the study exhibits weak geological condition, lithological composition, tectonic activity, oversaturation of soil mass, high precipitation and anthropogenic factors are the major causes of the landslide. According to the field assessment and the type of slope failures, the landslide is unstable, particularly during the rainy season. General recommendation incorporates structural and non-structural techniques to minimize the risk and mitigate the landslide hazard.